Effect of Chicken Manure Rate and Biofertilizer Concentration on the Growth and Yield of Land Kale Plants (Ipomea reptans Poir.) - Rahayu, Sulistyowati Puji; Amalia, Lia; Widodo, R Wahyono (Institute of Computer Science (IOCS), 2022)
This study aims to study the interaction between the dose of chicken manure and the concentration of biofertilizers on growth And concentration of biological fertilizers on the growth and yield of kale and want to know the optimum dose of chicken manure and the concentration of biological fertilizers that have the best effect on water spinach plants. The experiment was conducted in Cisondari Village, Pasirjambu District, Bandung Regency, West Java Province. with an altitude of 1200 meters above sea level, Latosol soil type with a pH of 6.21 (slightly acidic). The experimental design used a factorial randomized block design (RBD) consisting of two factors and was repeated twice. The first factor is the dose of chicken manure which consists of four levels, namely: a0 = Control (0 g/polybag); a1=15g/poly bag; a2 = 30 g/polybag and a3 = 45 g/polybag). The concentration of Extragen Biological Fertilizers (E) consists of 4 levels, namely: e0 = Control (0 ml/liter); e1 = extragen (3 ml/liter); e2 = extragent (6 ml/liter) and e3 = extragent (9 ml/liter). The results of this study are: 1). There was no interaction between the application of chicken manure and the concentration of extragen biofertilizers on the growth and yield of ground kale. 2). The results of independent analysis of chicken manure application had a significant effect on plant height at 30 HST. number of leaves aged 15 HST, plant dry weight and root loss ratio. Meanwhile, the concentration of extragen biological fertilizers had a significant effect on plant height at 30 HST and plant fresh weight. 3). The optimum dose of chicken manure was found in treatment a3, namely 45 tons/ha, and the optimum concentration of extragen biofertilizer, namely 3 ml/liter for fresh weight, and 9 ml/liter of water for plant height of ground kale